From Isolation to Innovation: Narrative Self-Study of Teachers Adopting Digital Pedagogies in Remote Canadian Regions - Olivia Davis; Benjamin White; Charlotte Brown (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. Teachers in remote Canadian regions have historically faced challenges related to geographic isolation, limited access to professional development, and infrastructural disparities. The COVID-19 pandemic accelerated the demand for digital pedagogies, forcing educators in these contexts to rapidly adopt unfamiliar technologies and reconfigure their instructional practices. Purpose. This study investigates how teachers in remote areas navigated this transition through a narrative self-study lens. Method. Using qualitative methodology, five educators from rural provinces in Northern Canada engaged in self-reflective journaling and peer dialogue over a nine-month period. Thematic analysis of the narratives revealed key tensions between professional isolation and digital empowerment, as well as shifts in teacher identity, agency, and pedagogical innovation. Results. Participants described initial resistance, technological uncertainty, and emotional fatigue, which gradually evolved into adaptive strategies, collaborative learning, and renewed professional purpose. The findings highlight how digital transformation, though initially disruptive, served as a catalyst for reflective growth and community-building in marginalized teaching environments. Conclusion. The study concludes that narrative self-study can be a powerful tool for supporting teacher resilience, agency, and innovation, especially in geographically and technologically constrained settings.